Либертаризм и мораль - Дышкант, Татьяна Николаевна (Харківський національний університет ім. В. Н. Каразіна, 2013)
На современном этапе развития общества либертарианское направление становится доминирующим, не только в области экономики, но и во всех иных сферах общественной жизни. Поскольку неолибералы доводят свой экономический либерализм до этической спецификации, возникает потребность анализа практической философии неолиберализма. Сделан вывод о непоследовательности неолибералов в разработке своей системы ценностей, что приводит к исчезновению даже такого основополагающего понятия как свобода.

On the modern stage of development of society libertarian direction becomes dominant, not only in area of economy but also in all other spheres of public life. As libertarians takes the economic liberalism to ethics specification, there is the necessity of analysis of practical philosophy of libertarianism. The freedom understood as independence is the fundamental value of this direction. The open market built on principles of honest competition and presence of private property can secure her only. The presence of all above-mentioned conditions by unintentional way will provide a beneficence societies and spiritual development of man. However by the basic law of the society built exceptionally on a market exchange without taking into account social component, there is the law of maximal profits. It is instrumental in that market, all farther walks away from procedural honesty. There are processes which are instrumental in elimination, both freedom of markets processes and individual freedom. A conclusion is thus done about inconsistentness of libertarians in development of the system of values that results in disappearance even such fundamental concept as freedom.
Libertarism and moral
Keywords: общество; неолиберальная система ценностей; концепция свободы; индивид; индивидуализм; свободный рынок; free market; negative freedom; individualism